River Geography of the State of Bosnia in the Notes of Evliya Çelebi - Yıldırım, Filiz (Van Yüzüncü Yıl Üniversitesi, 2022)
Banks and basins of streams and rivers have been identified as the most suitable areas for settlements thought human history. This is because water, which is the most basic need of humans, is required not only for agricultural activities but also for the sustainability of various enterprises, such as mills. Coastal areas have been chosen despite the danger of flooding and roads have been built in these regions to render them more habitable. Bridges built on rivers are of commercial and military significance. Additionally, the fact that they are means of meeting civilizations and cultural fusions make these structures and their locations rather valuable. Furthermore, over time, a structuring has started from the coastal areas toward the interior, which resulted in a prosperous image. The geography of Bosnia, where Evliya Çelebi was located during the early 17th century, constitutes one of the strategic places in the Balkans. There are numerous rivers in Bosnia, where almost every inch of the land is fed by streams. The paths of many of these rivers intersect and head in the same direction, towards the Sava River, which is considered the northern border of the Balkans. The rivers feeding the opposite direction of this geography and pouring into the Adriatic Sea also decorate the Dalmatian basin. The main source of this study is Evliya Çelebi's Seyahatnâme. The information about the rivers identified in this valuable book was brought into being by being supported by various sources. The subject of this study, which is a monographic study, was discussed in the context of historical geography. It is thought that the subject related to this will contribute to the branches of onomastics and one of its subfields, toponymy, as well as to the science of hydrography.

Akarsu kıyıları ve havzaları, insanlık tarihi boyunca yerleşim için en uygun mahaller olarak tespit edilmiştir. Zira insanın en temel ihtiyaçlarından olan suya tarımsal faaliyetler için ihtiyaç duyulduğu kadar, değirmen gibi çeşitli işletmelerin varlığını sürdürmesi için de gerek duyulmuştur. Kıyı bölgeleri, taşkın tehlikesine rağmen tercih edilmiş, buralarda yollar yapılarak daha yaşanılır hale getirilmiştir. Nehirler üzerinde inşa edilen köprüler, ticari ve askerî açıdan önem taşımaktadır. Yine medeniyetlerin tanışmasına, kültürel bir kaynaşmaya vesile olması bu yapıları ve bulunduğu mevkileri değerli kılmaktadır. Öyle ki zamanla kıyı bölgelerinden iç kısımlara doğru bir yapılaşma başlamış ve mamur bir görüntü elde edilmiştir. Evliya Çelebi’nin 17. yüzyılın başlarında bulunduğu Bosna coğrafyası, Balkanların en stratejik yerlerinden birini oluşturmaktadır. Neredeyse her karış toprağının akarsularla beslendiği Bosna’da, çok sayıda nehir bulunmaktadır. Bu nehirlerden birçoğunun yolları kesişmekte ve aynı yöne yani Balkanların kuzey sınırı olarak kabul edilen Sava Nehri’ne doğru yol almaktadırlar. Bu coğrafyanın zıt istikametini besleyen ve Adriyatik Denizi’ne dökülen nehirler de Dalmaçya havzasını süslemektedir. Bu araştırmanın temel kaynağı Evliya Çelebi’nin seyahatnamesidir. Bu kıymetli eserde tespiti yapılan nehirler hakkındaki bilgiler, farklı birçok kaynak ile desteklenmek suretiyle vücuda getirilmiştir. Monografik bir çalışma olan bu araştırma konusu, tarihi coğrafya bağlamında ele alınmıştır. Bundan hareketle ilgili konunun onomastik ve onun bir kolu olan toponimi dallarına, aynı zamanda hidrografi ilmine de katkı sağlayacağı düşünülmektedir.
Evliya Çelebi Seyahatnâmesi'nde Bosna Eyaleti Nehir Coğrafyası